"You" or "We": The limits of the second‐person perspective. (28th July 2021) - Honneth, Axel
Abstract: The following paper questions the idea behind Stephen Darwall's attempt to ground all moral obligations in a perspective that he calls "second‐personal." In a first step, I will reconstruct Darwall's argument with the aim of raising doubt over whether the moral norms that supposedly govern interpersonal interactions in fact result from their reference to a "you, " as he claims, rather than from a reference to a collectively implied "we", as I shall go on to argue (1). Posing this question will then afford me an opportunity to look more closely at Hegel's implicit reservations about Fichte's doctrine of recognition, reservations which I find entirely persuasive (2). In a final step, I will return to Darwall's project. In my view, this project ultimately fails due to its denial of the social, and thus conflictual, character of the moral norms governing participants within the I–you relation (3).